Avaliação do efeito do extrato aquoso da folha de Syzygium cumini em modelo de toxicidade aguda por etanol in vivo - Cargnelutti, Lariane Oliveira (2015)
From the social use to problematic, ethanol is the most commonly drug used in the world. As it reaches almost all physiological systems, the ethanol consumption causes many physiological changes. The pharmacological and toxicological effects of ethanol depend on their concentration and their metabolites in the body, and the exposure time to these substances. Adenosine deaminase (ADA, EC 3.5.4.4) is considered a key enzyme in the metabolism of purines. It assists in the regulation of extracellular adenosine, which plays an important role in neuromodulation in the central nervous system and also in the release of inflammatory mediators acting on receptors in cells of the immune system. Furthermore, adenosine may play a crucial role in the mediation of many neuronal effects of ethanol. The Syzygium cumini (S. cumini), popularly known as jambolan, is a plant that has hypoglycemic, anti-inflammatory, antipyretic and antioxidant properties. Considering the many changes caused by acute excessive consumption of alcohol associated with the importance that the use of medicinal plants is to a great part of the population along with the great potential of therapeutic alternatives related to these plants, this study aimed to evaluate, by conducting an animal model of acute intoxication, the effect that a high dose of ethanol may cause to the ADA activity and to the levels of inflammatory mediators. At the same time, check the protective effect of the aqueous extract of the leaves of S. cumini (ASc) on the possible changes caused in the evaluated parameters. The results showed that after 6 hours of acute intoxication with ethanol, at a dose of 5g /Kg, the serum ADA activity, as well as of the spleen lymphocytes increases, whereas in the cerebral cortex was observed a decrease in this activity. When analyzing the levels of inflammatory mediators, the results showed that ethanol causes an increase in the release of inflammatory mediators IL-1, IL-6, TNF-α, INF-γ and NOx and a reduction of the anti-inflammatory cytokine IL-10. Beneficially, we found that the treatment with ASc, at a dose of 0.4g / kg, was able to prevent the changes caused by ethanol in the ADA activity and NOx and IL-10 levels. Thus, our results suggest that the action of ethanol on the purinergic system may be a mechanism by which ethanol exerts its effects on the release of inflammatory mediators and on the central nervous system, and that the ASC can minimize changes resulting from acute exposure to ethanol, since the reduction of ADA activity can affect various physiological and pathological.